Evaluation of Implementation of Gamification, Game-Based Learning, and Active Methodologies to the Flipped Classroom Model - Rojas-de-Gracia, María-Mercedes (2022)
The use of the flipped classroom at HE has been very popular in recent years. However, recently a series of studies are appearing that question in a certain way the usefulness of this methodology to improve student learning. To shed more light on this dichotomy, this study has been carried out, which presents as its main strengths the fact that it is a longitudinal investigation, with a large sample of students from various subjects and from two different countries. Its findings confirm that the degree of student satisfaction when the flipped classroom is applied with gamification and with active methodologies is very high, especially with regard to the use of Kahoot!, and the work of the teachers who apply them. Likewise, it is concluded that student satisfaction is slightly higher when the teachers who apply it do not do it alone, but rather do it collaboratively with other colleagues.